Breast conserving surgery in combination with intraoperative radiotherapy after previous external beam therapy: an option to avoid mastectomy - Thangarajah, Fabinshy; Winkelmann, Johanna; Wenz, Frederik; Sperk, Elena (Breast cancer research and treatment, 2018)
Mastectomy is the standard procedure in patients with in-breast tumor recurrence (IBTR) or breast cancer after irradiation of the chest due to Hodgkin’s disease. In certain cases a second breast conserving surgery (BCS) in combination with intraoperative radiotherapy (IORT) is possible. To date, data concerning BCS in combination with IORT in pre-irradiated patients are limited. This is the first pooled analysis of this special indication with a mature follow-up of 5 years.